1995
DOI: 10.1007/bf00401839
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin therapy: the clinical realities

Abstract: To evaluate metabolic control and safety parameters (hypoglycaemia frequency and nasal mucosa physiology), 31 insulin-dependent diabetic patients were treated with intranasal insulin at mealtimes for 1 month and with subcutaneous fast-acting insulin at meals for another month in an open, crossover randomized trial. During both treatment periods the patients were treated with intermediate-acting insulin at bedtime. Six of the patients were withdrawn from the study during intranasal insulin therapy due to metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 12 publications
0
21
0
4
Order By: Relevance
“…In a previous study, we showed that inhalation of an insulin powder aerosol containing solid insulin particles (99 U) led to a relative bioavailability of 7.8 ± 3.5% and a relative bioefficacy of 7.6 ± 2.9% (2). This bioefficacy was comparable with that achieved with nasal insulin administration using absorption enhancers but implies that a large amount of insulin has to be used with either administration form to achieve a sufficient metabolic effect (3)(4)(5)(6)(7). Nevertheless, the time-action profile seen with inhalation of insulin showed promising properties (i.e., a rapid onset of action and a relatively long duration of action).…”
mentioning
confidence: 79%
“…In a previous study, we showed that inhalation of an insulin powder aerosol containing solid insulin particles (99 U) led to a relative bioavailability of 7.8 ± 3.5% and a relative bioefficacy of 7.6 ± 2.9% (2). This bioefficacy was comparable with that achieved with nasal insulin administration using absorption enhancers but implies that a large amount of insulin has to be used with either administration form to achieve a sufficient metabolic effect (3)(4)(5)(6)(7). Nevertheless, the time-action profile seen with inhalation of insulin showed promising properties (i.e., a rapid onset of action and a relatively long duration of action).…”
mentioning
confidence: 79%
“…However, a study involving 31 subjects with type 1 diabetes found that the intranasal insulin dose needed to reach given markers of glycemic control was some 20 times higher than that of subcutaneous administration. Moreover, serum insulin concentrations increased more rapidly and declined more quickly during nasal administration than during subcutaneous administration (16). The authors concluded that intranasal insulin treatment was not a realistic alternative to subcutaneous insulin because of the low bioavailability and high rate of treatment failure.…”
Section: Intranasalmentioning
confidence: 99%
“…NovoNordisk made the first major attempt to bring a non-injectable insulin to market with nasal insulin. Experience soon showed that this was not a realistic alternative, for despite the advantage of rapid absorption, bioavailability was low (the nasal dose needed to be 20-fold greater than the injected dose) and the rate of treatment failure unacceptably high [7]. The success of insulin pens may also help to explain why the project was quietly dropped.…”
Section: Dangerous Safetymentioning
confidence: 99%